Giftedness as asynchronous development of children with special educational needs - Prokhorenko , Lesia Ivanivna (Insight: the psychological dimensions of society, 2022)
The research purpose is to clarify the featuresof asynchronous development of gifted children withpsychophysical disorders that will be a substantialargument for shaping a differentiated approach toteaching such children amidst inclusion. Methodologyand methods. It is substantiated that the methodologicalprovision is the interpretation of the phenomenonof giftedness as asynchronous development, whichstipulates special needs and provides for the creationof conditions for their satisfaction. It was applied a retrospectiveanalysis, generalization and systematizationof the scientific literature on the relevant problem;participation observation using the observation protocoland the author’s survey. The study participantsare inclusive classes with talented and gifted childrenwith special educational needs (n=100) and teachers(n=25) who maintain the organization of an inclusivespace and conduct classes with such students. Results.It was defined the features of asynchronous developmentof gifted children with special needs, as follows: specifics of motivational, cognitive and social components,involving the deficiency of cognitive and adaptiveskills, breach of socially acceptable norms, limitedcommunication, etc. An experimental model of giftednessresearch, which contains the features of a giftedperson at four levels: psychophysiological, psychological,socio-psychological and pedagogical, was elaborated.Conclusions. The main issues which need urgentaddressing were summarized, including adherence tothe principle of the best interests of gifted children withspecial needs and the application of a comprehensiveapproach to ensure their right to access to high-qualityeducational and social services. Emphasis was placedon the development of teaching & learning materialsfor alternative forms of education and the upbringingof gifted children.